2018
DOI: 10.1007/s12079-018-0478-y
|View full text |Cite
|
Sign up to set email alerts
|

Strontium inhibits osteoclastogenesis by enhancing LRP6 and β-catenin-mediated OPG targeted by miR-181d-5p

Abstract: Strontium is a drug with the bone formation and anti-resorption effects on bone. The underlying mechanisms for the dual effect of strontium on bone metabolism, especially for the anti-resorption effects remain unknown. Thus, we aim to investigate the mechanisms of effects of strontium on osteoclastogenesis. Firstly, we found that strontium decreased the levels of important biomarkers of receptor activator of nuclear factor kappa-B ligand (RANKL) which induced osteoclast differentiation, indicating that stronti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…See Table 1 for information about miR‐181 targets in each differentiation lineage. References: [1] (H. Li et al, 2013), [2] (Ouyang et al, 2016), [3] (Z. Zhang et al, 2019), [4] (Knarr et al, 2019), [5] (Chen, Shi, et al, 2016), [6] (Chen, Ning, et al, 2016), [7] (Henao‐Mejia et al, 2013), [8] (C. Z. Chen et al, 2004), [9] (Gabler et al, 2015), [10] (P. Y. Lv, Xu et al, 2020), [11] (Barter et al, 2015), [12] (Vail et al, 2022), [13] (Melnik et al, 2021), [14] (Bakhshandeh, Soleimani, Paylakhi, et al, 2012), [15] (Q. Zhang et al, 2022), [16] (R. Su et al, 2015), [17] (X. Li, Zhang, et al, 2012), [18] (Naguibneva et al, 2006), [19] (Wei et al, 2016), [20] (P. Yuan et al, 2022), [21] (He et al, 2022), [22] (Y. Wang et al, 2020), [23] (Z. Zhao et al, 2019), [24] (Cichocki et al, 2011), [25] (Bhushan et al, 2013), [26] (N. Liu et al, 2020), [27] (Bakhshandeh, Soleimani, Hafizi, et al, 2012), [28] (Zheng, Liu, Tycksen, Nunley and McAlinden 2019), [29] (P. Qi et al, 2021), [30] (P. Y. Lv, Gao, et al, 2020), [31] (Ma et al, 2020), [32] (Y. Liu et al, 2021), [33] (Xie et al, 2018), [34] (B. Zhang et al, 2021), [35] (Shao et al, 2015), [36] (Shao et al, 2018), [37] (Fu et al, 2021), [38] (Han et al, 2020), [39] (Yu et al, 2021), [40] (T. Sun et al, 2019), [41] (G. Liu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…See Table 1 for information about miR‐181 targets in each differentiation lineage. References: [1] (H. Li et al, 2013), [2] (Ouyang et al, 2016), [3] (Z. Zhang et al, 2019), [4] (Knarr et al, 2019), [5] (Chen, Shi, et al, 2016), [6] (Chen, Ning, et al, 2016), [7] (Henao‐Mejia et al, 2013), [8] (C. Z. Chen et al, 2004), [9] (Gabler et al, 2015), [10] (P. Y. Lv, Xu et al, 2020), [11] (Barter et al, 2015), [12] (Vail et al, 2022), [13] (Melnik et al, 2021), [14] (Bakhshandeh, Soleimani, Paylakhi, et al, 2012), [15] (Q. Zhang et al, 2022), [16] (R. Su et al, 2015), [17] (X. Li, Zhang, et al, 2012), [18] (Naguibneva et al, 2006), [19] (Wei et al, 2016), [20] (P. Yuan et al, 2022), [21] (He et al, 2022), [22] (Y. Wang et al, 2020), [23] (Z. Zhao et al, 2019), [24] (Cichocki et al, 2011), [25] (Bhushan et al, 2013), [26] (N. Liu et al, 2020), [27] (Bakhshandeh, Soleimani, Hafizi, et al, 2012), [28] (Zheng, Liu, Tycksen, Nunley and McAlinden 2019), [29] (P. Qi et al, 2021), [30] (P. Y. Lv, Gao, et al, 2020), [31] (Ma et al, 2020), [32] (Y. Liu et al, 2021), [33] (Xie et al, 2018), [34] (B. Zhang et al, 2021), [35] (Shao et al, 2015), [36] (Shao et al, 2018), [37] (Fu et al, 2021), [38] (Han et al, 2020), [39] (Yu et al, 2021), [40] (T. Sun et al, 2019), [41] (G. Liu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, antiosteoclastogenic function was reported following overexpression of miR‐181b (Han et al, 2020) and miR‐181c (Yu et al, 2021). For miR‐181d, one report described mimic‐induced enhancement of osteoclast differentiation via targeting and suppression of OPG (T. Sun et al, 2019).…”
Section: Expression and Function In Skeletal Cell Differentiationmentioning
confidence: 99%
“…The reduced positivity of the OC differentiation markers in the case of Coll/MBG_Sr4% material may be due to the presence of Sr 2+ . Indeed, Sr 2+ interferes with OC differentiation by acting on several molecular pathways, as shown by Sun et al, who found fewer TRAP-positive cells and fewer multinuclear cells in Sr 2+ -treated cells [ 49 ]. Thus, the marked TRAP-positive response of pre-OCs on Coll/nano-HA material may be related to the absence of Sr 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…On day 2, the medium was replaced with fresh medium consisting of M-CSF, R.A.N.K.L., and sodium butyrate. Photos were captured using inverted microscopy Zeiss microscope and imaging system (Carl Zeiss Inc., Germany) [ 42 ].…”
Section: Methodsmentioning
confidence: 99%